Efficiency analysis of banks in ASEAN countries. Issue 7 (3rd October 2016) - Wong, Wai Peng; Deng, Qiang
Abstract : Purpose: The purpose of this paper is to explore various efficiency aspects of banks in Association of Southeast Asian Nations (ASEAN) in light of their remarkable growth in recent years. Design/methodology/approach: The authors used various data envelopment analysis technique to measure the relative efficiency for a sample of 39 banks in four ASEAN countries over 2000-2010. Findings: The analyses reveal three findings: first, Malaysian banks are more efficient comparatively to the other three ASEAN countries. Second, large-sized banks in ASEAN are less cost efficient. Third, government banks in the ASEAN region exhibit a substantial improvement in efficiency throughout the years, in contrast to the non-government banks. Originality/value: Efficiency analysis of banks in ASEAN countries, particularly covering this large period, that is, from 2000 to 2010 is very limited, in fact nil. Hence, this paper contributes to the finance and banking areas by providing a detail analysis of banks' performance in the ASEAN region. This paper thus provides powerful insights to policy makers and bank managers in setting appropriate strategy for financial institutions in the region.